A Critique on the Book Ideology and Ideological State Apparatuses - Rohollah Eslami; Elaheh Valizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Not only have the ideas of Marxism analyzed societies, but also shaped social action. Marxists have read each Marx's works in a number of ways, and claim to have provided the closest interpretation to Marx. In the meantime, Louis Althusser, a French neo-Marxist thinker of the twentieth century, with a structuralist reading, has considered Marx's second period of thought, which is scientific. This article addresses the question of how Marxism can be analyzed not only in its purely economic deterministic nature but also in the political aspect of states in Marxist analysis. In this regard, we have introduced and critically reread the book Ideology and Ideological State Apparatuses by Louis Althusser, translated by Mr. Roozbeh Sadra. The book has been criticized in terms of form and ideas. Theoretically, Althusser, on the one hand, determines the culture and ideological mechanisms of the state in socio-political developments and, on the other hand, promotes a kind of conspiracy illusion. The form of the book is desirable in terms of cover design and requires some writing corrections that are documented in the text.